iTRAQ®-based quantitative proteomics reveals the proteomic profiling of methicillin-resistant Staphylococcus aureus-derived extracellular vesicles after exposure to imipenem - Wang, Jichun; Wang, Junrui; Wang, Yanyan; Sun, Peng; Zou, Xiaohui; Ren, Luo; Zhang, Chunxia; Liu, Enmei (Folia microbiologica, 2021)
This study sought to reveal the proteomic profiling of methicillin-resistant Staphylococcus aureus (MRSA)-derived extracellular vesicles (EVs) after exposure to imipenem. The advanced isobaric tags for relative and absolute quantitation (iTRAQ®) proteomic approach were used to analyze the alterations in MRSA-derived EV protein patterns upon exposure to imipenem. A total of 1260 EV proteins were identified and quantified. Among these, 861 differentially expressed exosome proteins (P < 0.05) were found. Multivariate analysis, Gene Ontology (GO) annotation, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were used to analyze the identified proteins. Enrichment analysis of GO annotations indicated that imipenem primarily regulated the metabolic processes in MRSA. The metabolism of differentially expressed proteins was found to be the most significant in the combined analysis of the KEGG pathway analysis. Based on the results from the STRING analysis, 50S ribosomal protein L16 (RplP) and 30S ribosomal protein S8 (RpsH) were involved in the imipenem-induced MRSA-derived EVs. These results provide vital information on MRSA-derived EVs, increasing our knowledge of the proteome level changes in EVs upon exposure to imipenem. Moreover, these results pave the way for developing novel MRSA treatments.
Keywords: Proteomics; imipenem; Extracellular Vesicles; proteomika; Imipenem; extracelulární vezikuly; stanovení celkové genové exprese; Gene Expression Profiling; Methicillin-Resistant Staphylococcus aureus; methicilin rezistentní Staphylococcus aureus